PERAN GURU DALAM MENGEMBANGKAN SOSIAL EMOSIONAL DI KELAS B3 TK GEMBALA BAIK KOTA PONTIANAK - Ardiani, .; ., Halida; Lukmanulhakim, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to see the role of teacher in developing the Social emotional of children aged 5-6 years in class B3 of kingdegarten Gembala Baik Pontianak. the role of the teacher in developing the social emotional of consists: a) The role of the teacher as an inspirator, teacher invite children to visit somewhere related to learning b) The role of teachers as facilitators, teachers facilitate children learning media c) The role of the teacher as a model, teacher give example of good behavior in children d) The role of the teacher as a motivator, teachers enceorage children to be pessionate about learning e) The role of teachers as evaluators, teacher asses the childâ€™s learning. The development of early childhood that is expected to have the ability and competence as well as the learning outcomes to be achieved is the ability to recognize the environment, recognize nature, recognize the social environment, the role of society, and appreciate the social diversity and culture that exist around children and children are able to develop self-concept, positive towards learning, have good self-control and have a sense of empathy on the problems of others. Children in their development need stimulation from the teacher or the environment in developing their social emotional.Â Keyboard: Role of Teacher, Social Emotional